Standard Operating Procedures for Tugboat Clearance and Service Enhancement at Jepara Port - Rikman Sohriadhana; Hidayah, Hidayah; Ali Sulistyo Budi; Anton Novianto; Paiman, Paiman (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Background: Clearance in and clearance out procedures are critical components of port operations that directly affect service quality, vessel turnaround time, and port sustainability. Jepara Port, as a regional hub, faces challenges in implementing effective clearance procedures for tugboats, notably TB. Bintang Harbour 4009, operated by PT. Sinar Bintang Samudera. Original value: Prior research has extensively examined container terminal performance and green port policies, but limited studies address tugboat clearance processes in smaller regional ports, despite their strategic role in supporting larger maritime logistics chains and sustainable port development frameworks. Objectives: This research investigates the clearance in/out procedures at Jepara Port, analyzes their influence on service quality, and evaluates whether adherence to SOPs can enhance efficiency and sustainability within the context of integrated maritime policy frameworks. Methodology: A qualitative descriptive approach was employed, using semi-structured interviews, questionnaires, direct observations, and document analysis. Data were analyzed through thematic analysis, cross-group comparisons, and narrative synthesis, incorporating sustainability assessment frameworks. Results: Findings revealed that while SOPs exist, their implementation is hindered by documentation errors, inconsistent inter-agency coordination, and partial digitalization. These issues contribute to prolonged clearance times and reduced compliance rates. However, improvements in first-time-right documentation and single-channel digital communication were shown to significantly enhance clearance performance and environmental outcomes. Conclusions: Clearance procedures are more than administrative requirements; they are strategic levers for port service quality, sustainability, and maritime vocational education. Strengthening these procedures can improve efficiency, reduce emissions, enhance port resilience, and support sustainable maritime development goals.